The effect of religiosity on trainees’ reaction and motivation to transfer: Evidence from Malaysia - Abdul Rahim Zumrah; Kalsom Ali; Khalid, MY; Mokhtar, AN (Emerald Group Publishing Ltd, 2024)
Indexed by WOS